STUDY OF CONSTRUCTIVE DIMENSIONS OF KAPLAN HYDRO TURBINE IN VARIABLE WATER FLOWS - G. N. Uzakov; Z. E. Kuziev (Journals Park Publishing, 2023)
Presents the results of research on improving the efficiency of a new type of improved vertical-axis hydropower device for water flows coming out of pump units and used for cooling technological devices in enterprises in changing water flows. The angle of contact of the water flow b 1 entering the hydro turbine blade and b 2 leaving it with the blade, the method of determining the optimal angle of inclination of the blades is presented. Mathematical modeling uses Matlab/Simulink system. The values of the water consumption and the angle of contact of the water flowing into the blades were determined for the case where the water pressure was changed to 1...5 m and the power of the hydro turbine was changed to 5...25 kW. It is based on the possibility of providing uninterrupted electricity to autonomous or enterprises' small power consumers using this hydropower device.
Keywords: Kaplan hydro turbine, water consumption, water flow rate, Matlab/Simulink system, turbine rotation speed, inlet and outlet angles of water flow to blades.